The role of victims in criminal proceedings before the international criminal court (2010)
The role accorded to victims in the ICC proceedings is considered as the most significant feature of the Rome Statute. It is an acknowledgment that the interests of victims often differ from the interests of the Prosecution, which is primarily responsible for, and tasked with, ensuring that the interests of the society are protected. Extensive ICC jurisprudence has already ruled on several controversial areas which are of utmost relevance for shaping such role. The article analyzes this jurisprudence with a particular focus on who can become a participating victim before the ICC and what those victims can procedurally carry out. As a result, the article first analyses the already ample body of ICC case law in relation to the interpretation of the definition of victim provided for in Rule 85, and in particular: (i) whether deceased persons are included within the notion of natural persons; (ii) the necessary link between the victims and the charges; (iii) the relevant forms of victims´ “harm”; (iv) the distinction between “direct” and “indirect” victims; (v) the distinction between victims of the situation and victims of the case; and (vi) the reassessment of decisions by Pre-Trial Chambers on victims’ status by Trial Chambers (TCs). Subsequently, the article turns its attention to the implementation of the core provision of the system of victims’ participation in the ICC Statute (article 68 (3)), with a particular focus on: (i) the systematic versus the casuistic approach to the determination of the role of victims in situation and case proceedings; (ii) the role of victims in the stage of investigation of a situation; (iii) the role of victims in the pre-trial proceedings of a case; (iv) the role of victims in the trial proceedings of a case; and (v) the role of victims in the recharacterization of facts by the TCs.